(untitled) (Ibrahim Medical College Journal, 2016)
Squamous cell carcinoma of the gall bladder is rare. It accounts for less than 12.7 % of all cases of gall bladder cancer. Pure squamous cell carcinoma is even less common with a reported incidence of 3.3%. We present a case of 70 years-old man with decreased appetite, vomiting and fever associated with right upper quadrant pain for two months. Ultrasonography of the abdomen revealed a distended gallbladder with multiple calculi along with large hyperechoic area of sludge. Provisional diagnosis was cholelithiasis with empyema of gall bladder. Cholecystectomy was done. Histopathological examination revealed well to moderately differentiated squamous cell carcinoma of the gall bladder without evidence of metastasis. Ibrahim Med. Coll. J. 2014; 8(2): 61-63